Knowledge Process Outsourcing (KPO) Industry: Status and Prospects Affecting Its Growth in the Philippines - Mondejar, Hans Christian U.; Asio, John Mark R. (Future Science / FSH-PH Publications, 2022)
In the Knowledge Process Outsourcing market, the Philippines is slowly gaining traction as a genuine challenger. Despite the effect of the pandemic, BPO industries in the Philippines continue to advance, with a promising future in the years ahead. The study focuses on the KPO practices in the Philippine setting and the factors affecting them. The researchers used a descriptive cross-sectional design to analyze the factors affecting the KPO industries and their practices. This study used a purposive sampling technique to 100 supervisory and key account managers as respondents from six BPO firms with KPO services. This study included measures of central tendency and inferential statistics to determine the relationship between KPO practices and the factors affecting them. The result of the study shows that among the three (3) KPO practices, the provider capability gained the highest level, followed by client-retained capacity and contractual governance. In addition, among the four (4) factors affecting KPO practices, regulatory aspects got the highest level, followed closely by innovative elements, technological factors, and human resource factors. Moreover, the study observed low to moderate associations between the KPO practices and the factors. Finally, the technological aspect emerged as a predictor of industry KPO practices.